แนวคิดการพัฒนาครูวิทยาศาสตร์เพื่อการพัฒนาท้องถิ่นอย่างยั่งยืน: Science Teacher, Local Development for Sustainable - วิมุตติปัญญา จิตตวิสุทธิ์ (วารสารวิชาการ มหาวิทยาลัยราชภัฏอุตรดิตถ์, 2019)
The purpose of this research was to study the Concept of Science Teachers Development for Local Sustainable Development. The sample were 190 students, 1-5 grade in academic year 2018 of General Science, Faculty of Education, Bansomdejchaopraya Rajabhat University. The research instrument was a questionnaire with a consistency index was at 1.00 discrimination was between 0.64 - 0.82 and a reliability was at .84. The statistics used for data analysis are frequency, percentage, and standard deviation for approximate data qualitative data uses content analysis and descriptive summaries. The results show that the Concept of Science Teachers Development for Local Sustainable Development at the all highest level (=4.66, S.D.=0.73) and it was found that the knowledge and understanding at the highest level (=4.72, S.D.=0.66), the science process at the highest level (=4.65, S.D.=0.76) and the innovation was at the highest level (=4.62, S.D.=0.76). The potential of science teachers of learning management in the 21st century must be able to apply scientific knowledge to integrate with local wisdom by cultivating learners with scientific process skills to create technological innovations using by learning resources for local development with awareness of value and meaningful learning.